Arabic Phonological Interference: Contrastive Analysis of Arabic Phonemes Against Indonesian Phonemes in Non-Arabic Literature Department Students of Al-Azhar University - Ayu Sekarsari; Annisa Eka Putri Aullia; Nailah Kaltsum; Rofiqo Hasanah Saragih; Rosita Dongoran (Konsultan Jurnal Ilmiah Indonesia, 2024)
Phonological interference events may occur due to two-language contacts. An Arab and Indonesian interaction allows a language contact that can lead foreign language users to experience phonological and grammatical interferences. This study is focused on phonological interferences on non-Arabic students of the Al-Azhar University of Indonesia. The objective of this study is to provide information on phonemic interferences in novice Arabic learners. This study also gives merits to Arabic teachers in Indonesia to find appropriate learning methods and strategies. Descriptive method and contrastive method were employed in this study. Data collection was conducted using sound recordings on 12 students of 6 faculties by way of reading of Arabic phonemes. Based on the recordings, 14 consonant-tone interferences were found: /ġ/ realized as [g], /q/ realized as [k], /ś/ realized as [s], /ʕ/ realized as [?], /ŧ/ realized as [t], /z/ realized as [ṣ], /ṣ/ realized as [s], /x/ realized as [h] and [ħ]/ħ/ realized as [h], /đ/ realized as [d] and [ð], /ð/ realized as [z], /θ/ realized as [s], /ż/ realized as [z] and [ð], /h/ realized as [ħ]. Vowel interferences were found in 4 vowels: short /a/ vowel realized as [ɔ], long /a:/ vowel realized as [o], /i:/ realized as [i] and /u:/ realized as [u]. The most frequent deviations were found in consonant /ż/ realized as [z] and consonant /θ/ realized as [s] as much as 29.76%. The interference level of each respondent was influenced by two things: the duration of learning and the frequency of day-to-day language use.